The new way to educate young adult on road safety using motion graphic / Mohamad Khamarul Muzamil Khalid - Khalid, Mohamad Khamarul Muzamil (Faculty of Art and Design, 2015)
Video has been synonymous with our daily lives, sometimes we forget how strong the power of the video can be. From displaying wonderful moment with love ones to the important message that can determine the fate of a nation all that can be delivered thru video. Now video is one of the most important medium to deliver message. Although video is a powerful tool it is useless unless the message that being sent won't reach the target audience. Making video is so simple with the press of a button (rec) on recording device a video is in the making they are many type of video now days from the movie that cost millions of dollar to home video that cost almost nothing.